"Freedom of Information in the Classroom: Teaching for Empowerment in the Social Sciences and in Ethnic Studies". Issue 2 (3rd April 2022) - Le, Loan K.
Abstract: This article describes public records request assignments in courses in political science and in Asian American Studies. Beyond commonly known activities like voting, volunteering, signing petitions or peacefully protesting, students should gain experience in exercising their rights to an expansive set of government records that fall within the domain of "the people's business." Few courses include public records requests (e.g., implementation of the Freedom of Information Act (FOIA) and state sunshine laws) as part of formal coursework assignments at the undergraduate level, although responsive records would be useful in, for example, course papers and in class oral history projects. For scholars of Asian American Studies, the FOIA can be used to uncover invaluable data and information that would otherwise be unavailable in traditional scholarly publications, textbooks, news articles and online posts. More generally, many students report that they are more interested in politics, knowledgeable and empowered regarding their political efficacy, as well as critical of bias in information flows from pundits in the media and from other sources after completing FOIA exercises.